INVESTIGATION OF IN-VITRO GASTROPROTECTIVE AND ANTIOXIDANTS EFFECTS OF MIMOSA PUDICA AND SESBENIA GRANDIFLORA - Prithivirajan Senthilkumar; ²Dhanasekar J; Snehal Dasharath Pawar; Lathamani Lakshmanan; Nandhakumaran S,; Arvinthkumar R; Ruban S; Poongodi Ranganathan (The Bioscan, 2026)
Gastric ulcer disease, a widespread condition driven by oxidative stress and acid imbalance, necessitates safer, multi-targeted therapies. This study investigated the gastroprotective potential of two traditional medicinal plants, Mimosa pudica (MPE) and Sesbania grandiflora (SGE), through in vitro assays.